2015
DOI: 10.1158/1055-9965.epi-15-0052
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use and Survival from Lung Cancer: A Population-Based Cohort Study

Abstract: Background: Preclinical evidence from lung cancer cell lines and animal models suggest that statins could have anticancer properties. We investigated whether statin users had reduced risk of cancer-specific mortality in a population-based cohort of lung cancer patients.Methods: Newly diagnosed lung cancer patients, from 1998 to 2009, were identified from English cancer registry data and linked to the UK Clinical Practice Research Datalink, providing prescription records, and to Office of National Statistics mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 24 publications
3
100
0
Order By: Relevance
“…Importantly, TCGA data suggest that the R270H-dependent MVA pathway GOF may be shared by other DNA contact mutants in human lung tumors. Notably, while the effects of statins on cancer remain controversial (Mullen et al 2016), there are reports of improved survival among statin-treated lung cancer patients (Cardwell et al 2015;Lin et al 2016). Based on our findings, it would be important to determine whether mutant p53 status is associated with that benefit.…”
Section: Discussionmentioning
confidence: 78%
“…Importantly, TCGA data suggest that the R270H-dependent MVA pathway GOF may be shared by other DNA contact mutants in human lung tumors. Notably, while the effects of statins on cancer remain controversial (Mullen et al 2016), there are reports of improved survival among statin-treated lung cancer patients (Cardwell et al 2015;Lin et al 2016). Based on our findings, it would be important to determine whether mutant p53 status is associated with that benefit.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, treatment with aspirin would be expected to weaken the association between MI and long-term cancer [35][36][37]. Studies on statin treatment and future development of cancer are inconsistent: Some studies have observed that use of statins may reduce both the risk of developing cancer and the rates of cancer-specific mortality for several cancer types [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…As described previously [15], we utilised record linkages between the English National Cancer Data Repository (NCDR) and the United Kingdom (UK) Clinical Practice Research Datalink (CPRD) to identify lung cancer patients diagnosed between 1998 and 2009. Office of National Statistics (ONS) mortality data provided deaths up to 2012.…”
Section: Methodsmentioning
confidence: 99%